QSAR DAN MOLECULAR DOCKING SENYAWA DERIVAT LUMIRACOXIB, INHIBITOR OKSIGENASI 2-AG PADA TERAPI INFLAMASI - Nursalam Hamzah; Haeria Haeria; Nurul Muhlisa Mus (Jurnal Farmasi UIN Alauddin Makassar, 2015)
Cyclooxygenase-2 (COX-2) is a molecular target that is widely studied and has a crucial role in the last decade. The high contribution of COX-2 in inflammation and inhibiting function of 2-AG oxygenation by COX-2 inhibitors in inflammatory, open a new chapter dealing with the research on inhibition of COX-2. The purpose of this study is to determine the physical-chemical properties that play an important role in the activity of lumiracoxib derivates based QSAR equation and look from the interaction of ligand-receptor through docking simulations. Statistical analysis was calculated by multilinear regression analysis using SPSS Statistics 17.0. Leave One Out cross validation, Pearson correlation, and the relationship of IC50 experiments and IC50 predictions curve are used to obtain QSAR equation with significantly statistic criteria. Molecular docking to study ligand-receptor interactions, performed using MOE 2009.10. Hydrogen bonds with amino acid residues on the receptor 4OTY include Ser A530 and Tyr A385 with the best scoring value in compound 8 is -8.0976 and the receptor 3HS6 include Ser A530, Tyr A385, Tyr A355 with the best scoring value in compound 1 is -6.34934. QSAR models show the best QSAR equation: Log (1/IC50) = -92.2384 + 0.5327 AM1_dipole + (-0.00049) AM1_E + 13.3123 log S + 35.7654 mr + (-0.5770 VSA).